Characterization of New Baker’s Yeast Strains And Their Leavening Ability in Bread Dough - Chakamas Wongkhalaung; Malai Boonyaratanakornkit (Agriculture and Natural Resources, 2007)
Two new Baker’s yeast strains obtained from hybridization of commercial baker’s yeast parent strains, Saccharomyces cerevisiae IFRPD 6080 and IFRPD 6081 with Japanese mating strains were investigated. The hybrids, IFRPD 6171 from parent strain 6080 and IFRPD 6173 from parent strain 6081, were evaluated for their characteristics, namely growth, total carbohydrate and trehalose contents, sugar fermentation ability, cryoresistance at -20 °C and their leavening ability in bread doughs. Both hybrids had good growth and higher maltose and sucrose fermentation abilities than their parents. Carbon dioxide productions in non-sugar, low-sugar and high-sugar dough were also markedly improved. In addition, hybrid 6171 possessed cryoresistance or freeze-tolerant ability in low-sugar dough and could be used for frozen dough preparation. Quality evaluation of white and sweet breads made from hybrids also showed better quality than their commercial parent strains. Thus, the hybrid 6171 was suitable for both white (low-sugar) and sweet breads (high-sugar) whereas hybrid 6173 was particularly good for sweet bread. Moreover, hybrid 6173 was also high in maltose fermentation ability and produced very high carbon dioxide in non-sugar dough, which indicated favorable characteristic to be used in nonsugar bread such as French bread.